Prevalence of Anemia in Children Aged Six Months to Thirty Six Months - A Hospital Based Study - Quaderi, Humaira Rafiqa; Hoque, Md Mahbubul; Ahmed, Nawshad Uddin; Begum, Dilruba; Debnath, Bithi (Bangladesh Journal of Child Health, 2017)
Background: Anemia is a common problem in childhood, especially children aged 6months to 24 months old. In Bangladesh overall, 68 % of children aged 6-59 months are anemic. Anemia impairs normal development, decreases physical exercise tolerance & intellectual performance in children which may lead to a slowdown of growth in children. It constitutes a major public health problem in young children in the developing world with wide social & economic implications. Objective: To see the prevalence of anemia among hospitalized children aged 6 months to 36 months. Methodology: Children 6 months 36 months aged who were admitted in Dhaka Shishu (Children) hospital due to some acute illness, were enrolled from 1st June, 2010 to 30th August, 2010. Children were classified as anemic when Hb level was <11gm/dl. On the values of MCV and morphology of RBC anemic babies were further classified as microcytic anemia, normocytic anaemia and macrocytic anaemia. Again in children with microcytic hypochromic RBC, serum ferritin, Hb electrophoresis, stool R/E and c-reactive protein were done to find out the cause. Results: Among 331 admitted children, 201(61%) children had anemia (Hb <11gm/ dl), Male was 123(61.2%) and female was 78(38.8%). Mean hemoglobin concentration was 9.2±1.2 gm/dl. Mild, moderate, severe anemia were19%, 39.3% and 2.4% respectively. The most affected age group was 6-23 months(76%). Microcytic anemia, macrocytic anemia, and normocytic anemia were present in 101(50.2%), 10(5%) and 90(44.8%) cases respectively. Among the microcytic hypochromic anemia, IDA was found in 60(59.4%), which was 29.85% among total anemic children. Conclusion: A large proportion of hospitalized children under 3 years were found anemic. Raising awareness of the problem and providing health care education in this group will be the key strategies to prevent and control this huge public health problem in Bangladesh. Bangladesh J Child Health 2016; VOL 40 (2) :98-102